Identification of extreme motor phenotypes in Huntington's disease. Issue 3 (21st November 2016) - Braisch, Ulrike; Hay, Birgit; Muche, Rainer; Rothenbacher, Dietrich; Landwehrmeyer, G. Bernhard; Long, Jeffrey D.; Orth, Michael
Abstract : The manifestation of motor signs in Huntington's disease (HD) has a well‐known inverse relationship with HTT CAG repeat length, but the prediction is far from perfect. The probability of finding disease modifiers is enhanced in individuals with extreme HD phenotypes. We aimed to identify extreme HD motor phenotypes conditional on CAG and age, such as patients with very early or very late onset of motor manifestation. Retrospective data were available from 1, 218 healthy controls and 9, 743 HD participants with CAG repeats ≥40, and a total of about 30, 000 visits. Boundaries (2.5% and 97.5% quantiles) for extreme motor phenotypes (UHDRS total motor score (TMS) and motor age‐at‐onset) were estimated using quantile regression for longitudinal data. More than 15% of HD participants had an extreme TMS phenotype for at least one visit. In contrast, only about 4% of participants were consistent TMS extremes at two or more visits. Data from healthy controls revealed an upper cut‐off of 13 for the TMS representing the extreme of motor ratings for a normal aging population. In HD, boundaries of motor age‐at‐onset based on diagnostic confidence or derived from the TMS data cut‐off in controls were similar. In summary, a UHDRS TMS of more than 13 in an individual carrying the HD mutation indicates a high likelihood of motor manifestations of HD irrespective of CAG repeat length or age. The identification of motor phenotype extremes can be useful in the search for disease modifiers, for example, genetic or environmental such as medication. © 2016 Wiley Periodicals, Inc.